IDNLearn.com is designed to help you find the answers you need quickly and easily. Join our platform to receive prompt and accurate responses from experienced professionals in various fields.
Sagot :
To find the inverse of the function [tex]\( f(x) = 5x \)[/tex], we need to follow these steps:
1. Definition of the Function:
We start with the given function [tex]\( f(x) = 5x \)[/tex].
2. Rewrite using [tex]\( y \)[/tex]:
To find the inverse function, we'll rewrite [tex]\( f(x) \)[/tex] as [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
3. Solve for [tex]\( x \)[/tex]:
We need to solve this equation for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
Divide both sides of the equation by 5 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{y}{5} \][/tex]
4. Express the Inverse Function:
Since [tex]\( x = \frac{y}{5} \)[/tex], we can write the inverse function [tex]\( f^{-1}(x) \)[/tex]. To match the notation, replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] in our final expression:
[tex]\[ f^{-1}(x) = \frac{x}{5} \][/tex]
5. Select the Correct Option:
Among the given options:
- [tex]\( f^{-1}(x) = -5x \)[/tex]
- [tex]\( f^{-1}(\pi) = -\frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = 5x \)[/tex]
The correct option is:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
Therefore, the correct answer is the third option:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
1. Definition of the Function:
We start with the given function [tex]\( f(x) = 5x \)[/tex].
2. Rewrite using [tex]\( y \)[/tex]:
To find the inverse function, we'll rewrite [tex]\( f(x) \)[/tex] as [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
3. Solve for [tex]\( x \)[/tex]:
We need to solve this equation for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ y = 5x \][/tex]
Divide both sides of the equation by 5 to isolate [tex]\( x \)[/tex]:
[tex]\[ x = \frac{y}{5} \][/tex]
4. Express the Inverse Function:
Since [tex]\( x = \frac{y}{5} \)[/tex], we can write the inverse function [tex]\( f^{-1}(x) \)[/tex]. To match the notation, replace [tex]\( y \)[/tex] with [tex]\( x \)[/tex] in our final expression:
[tex]\[ f^{-1}(x) = \frac{x}{5} \][/tex]
5. Select the Correct Option:
Among the given options:
- [tex]\( f^{-1}(x) = -5x \)[/tex]
- [tex]\( f^{-1}(\pi) = -\frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = \frac{1}{5} x \)[/tex]
- [tex]\( f^{-1}(x) = 5x \)[/tex]
The correct option is:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
Therefore, the correct answer is the third option:
[tex]\[ f^{-1}(x) = \frac{1}{5} x \][/tex]
We appreciate every question and answer you provide. Keep engaging and finding the best solutions. This community is the perfect place to learn and grow together. IDNLearn.com has the answers you need. Thank you for visiting, and we look forward to helping you again soon.